Invasion, retaliation, concealment and silences at Dead Man's Flat, South Australia: A consideration of the historical, archaeological and geophysical evidence of frontier conflict. Issue 2 (3rd July 2021) - Roberts, Amy; Barnard-Brown, Jessica; Moffat, Ian; Burke, Heather; Westell, Craig; Aboriginal Corporation, the River Murray and Mallee
ABSTRACT: This article presents the results of historical research, as well as archaeological and geophysical surveys, in order to explore a number of frontier conflict events at Dead Man's Flat in South Australia (SA). The historical records reveal the cruelty and complexity of the period and expose the concealments, contradictions, euphemistic language, denials and silences that are typical of the Australian frontier. Further disparities are revealed in more recent commemorative efforts. Archaeological investigations in the study area provided an 'absence of evidence'. Whilst the geophysical survey revealed that there are potential graves located on the flat, no interment was located in the area commemorated by local non-Indigenous community members. The combined results of this multi-method approach uncovered new dissonances, raised new questions and provided new exegeses about the frontier in this region. For traditional owners, the sum of the evidence reveals a history of invasion, killings and massacre, theft, deceit and cover-up – Dead Man's Flat is, therefore, a place to be approached with deep respect in order to honour the experiences of their ancestors.